The Phenomenon of Ambiguity in Contemporary Algerian Poetry within the Algerian Critical Experience - MOUS, Nadjia (Journal of Ecohumanism, 2026)
The phenomenon of ambiguity has become a defining feature of contemporary Arabic poetry, creating a significant gap between the poet and the reader. This has led to ongoing debates among poets, readers, and critics regarding the language of this poetry, as well as whether this ambiguity is intentional or spontaneous, a mere stylistic choice or an act of creativity. Contemporary Algerian poetry has not been exempt from this trend, as it has undergone numerous transformations, both artistic and aesthetic. These changes have expanded its intellectual and epistemological vision, opening its semantic horizon to diverse readings and interpretations. The text now presents symbolic images that challenge the reader’s understanding, encouraging multiple interpretations. Against this backdrop, our research, titled "The Phenomenon of Ambiguity in Contemporary Algerian Poetry in the Algerian Critical Experience," falls under the first axis (modern Algerian poets and critics). The study aims to address the following question: How does the Algerian critic interpret the ambiguous Algerian poetic text? Is this a local reading, or is there an external authority shaping it? The research further seeks to explore the aesthetics of the contemporary Algerian poem as presented to the attentive reader.